Developing value creation framework for Malaysia’s aluminium recycling industry from construction perspective - Rakiman, Umol Syamsyul (2018)
Understanding on how value is created in certain product, service or firm is a precious knowledge. Value chain analysis is an original framework to explain value creation. But certain product or service could not be explained by this framework as it is more suitable for manufactured product. Nowadays aluminium is replacing steel in many of our daily products and it is an indefinitely recyclable item. The aim of this research is to develop a framework to explain value creation in aluminium recycling industry. Eight (8) case studies were selected which represents the actors in the aluminium recycling value chain. Respondents were from the construction site, metal collectors and many more. From these case studies, the activities which create value in the aluminium recycling value chain had been identified. The activities can be divided into primary and supporting activities. Primary activities are the activity which directly affects the value of the aluminium in the recycling chain. While supporting activities are the activities which affect the primary activities in value creation. However, the activities of aluminium recycling value creation are not similar as in the value chain analysis. Most notably recycling does not have marketing in the value creation framework. Moreover, aluminium recycling value creation framework has prerequisite factor which allows primary and secondary activities to work together to create value. The prerequisite factor consists of quality, quantity and government policy. This understanding may help the recycling industry in general to be more competitive. Highlighting the value aspect into recycling will result in environmental awareness no longer seen as a good deed only but as a promising business that can't be ignored. The knowledge on the value creation from the recycling process can attract ventures and investment towards the recycling activity.